MR1-Restricted Mucosal-Associated Invariant T Cells and Their Activation during Infectious Diseases - Howson, Lauren J.; Salio, Mariolina; Cerundolo, Vincenzo (Frontiers in Immunology, 2015)
MR1-restricted mucosal-associated invariant T (MAIT) cells recognize vitamin B metabolites, which are generated by a broad range of bacteria, from Escherichia coli to Mycobacterium tuberculosis and BCG. MAIT cells have been described as innate sensors of infection as they accumulate early in infected tissues. MAIT cells maintain an activated phenotype throughout the course of infections, secrete inflammatory cytokines, and have the potential to directly kill infected cells, playing an important role in shaping the host response. In this review, we will discuss the current knowledge regarding the molecular mechanisms that underline MAIT cells activation in sterile and non-sterile inflammatory conditions.